A Case Study: Application of Kersen Leaf Extract (Muntingia Calabura L.) and Manuka Honey Ointment Combination On Second Degree Superficial Burns - Shella Oktavia Cahyaningrum; Estrin Handayani; Eka Sakti Wahyuningtyas; Ratna Wijayatri (LPPM Universitas Harapan Bangsa, 2024)
Background: Burns are a significant cause of morbidity and mortality globally. Intensive treatment is necessary to prevent infection and manage erythema in burn wounds. This case study aims to evaluate the effectiveness of a combination ointment containing Kersen (Muntingia calabura L.) leaf extract and Manuka honey in treating second degree superficial burns. Methods: A case study design employing evidence-based practice was used. Data were collected through interviews, observations, and physical examination. The study was conducted from October 14-28, 2023 in Mirikerep Hamlet, Pringsurat Village, Temanggung Regency, Indonesia. A comprehensive nursing care approach was implemented, including assessment, diagnosis, intervention, implementation, and evaluation. Results: Macroscopic examination revealed a significant reduction in wound area from 5.5x3 cm to 0.5x0.3 cm after treatment with the combination ointment. The ointment effectively promoted epithelialization and tissue regeneration in the healing process of second-degree superficial burns. Conclusions: The combination ointment containing Kersen leaf extract and Manuka honey demonstrates potential as an effective treatment for second degree superficial burns. Further research is warranted to elucidate the mechanisms underlying its therapeutic effects.